Potencial alelopático de extrato etanólico de anadenanthera macrocarpa e astronium graveolens - Silva, Regildo Márcio Gonçalves [UNESP]; Saraiva, Thiago Silvestre [UNESP]; Silva, Renato Boreli [UNESP]; Gonçalves, Lucivane Aparecida [UNESP]; Silva, Luciana Pereira [UNESP] (My University, 2010)
The objective of this study was to evaluate the allelophatic potential ethanol extract of leaves of Anadenanthera macrocarpa (Benth.) Brenan (angico) and Astronium graveolens Jacq (aroeira) on the biomonitor germination of Brassica chinensis (Malaysia's cabbage) and Lactuca sativa (lettuce). For the test of allelopathy was the bioassay of germination of B. chinensis and L. sativa using solutions of ethanol extracts in different concentrations (5, 10 and 20 mg / mL) with continuous light for 11 days. The experimental and control groups were divided into the Petri dish containing 50 seeds of B. chinensis and L. sativa each. Were performed six replicates for each concentration of extract of leaves of A. macrocarpa and A. graveolens and the negative control (water). The rolling action of the treatments was performed by quantitative observation and monitoring of germination every six hours. The results show that the ethanol extract of A. macrocarpa and A. graveolens presents allelopathic potential, regardless of the concentration used, but with answers dose-dependent, and thus able to interfere directly in germination, average speed and time of germination biomonitor of B. chinensis and L. sativa.
Allelopathy potential of etanolic extract of anadenanthera macrocarpa and astronium graveolens
Keywords: Allelopathy. seed germination. angico. aroeira